Rencana Strategis BKPSDM Kabupaten Solok: Analisis SWOT untuk Peningkatan Kinerja Sumber Daya Manusia - Vanny Nuary Winanda; Syafwandi (Jurnal Riset Multidisiplin Edukasi, 2025)
This study analyzes the strategic planning of the Human Resources Development and Personnel Agency (BKPSDM) in Solok Regency using SWOT analysis to enhance human resource performance. A qualitative method was employed, with data collected through in-depth interviews, observation, and official document studies. Key findings identify strengths in human resource quality and information systems, while weaknesses include budget constraints and bureaucratic inefficiency. Opportunities lie in external collaboration and technology adoption, whereas threats encompass inter-regional competition and regulatory changes. The strategic plan, formulated via TOWS matrix, prioritizes training capacity building, service digitization, and inter-institutional synergy. Implementation is measured through key performance indicators such as employee competency growth and recruitment efficiency. The study recommends accelerating digital transformation and performance-based budgeting for sustainable HR policy.